Akibat Hukum Bagi Notaris Terhadap Penyalahgunaan Keadaan Dalam Pembuatan Akta Autentik - Rifandika Naufal Afif; Andi Muh Ihsan; Dita Elvia Kusuma Putri (Jurnal Ilmu Kenotariatan, 2024)
In its development, the lawsuit for canceling e agreement due to the absence agreement as included in first condition Article 1320 of the Civil Code, is not limited to Article 1321 of the Civil Code, such as oversight, coercion and fraud, but in its development new reasons emerge, namely misbruik van omstandigheiden. In practice, raising questions related to classification can be categorized abuse of circumstances and the notary's responsibility in a deed that is proven to have an abuse of circumstances. This study to analyze the legal consequences of misuse of circumstances in making authentic deeds for notaries. The legal issues, are, 1) First, the criteria abuse circumstances in making an authentic deed, 2) Second, the responsibility of the notary an authentic deed which was canceled due to a misuse of circumstances. This research is a normative research with a statutory approach, a conceptual approach, and a case approach. Based on this research, it was found that First, the criteria for misuse of circumstances in a notarial deed include: a. There is a loss suffered by one party; and b. There was abuse of opportunity by the parties at the time of the agreement, both economic and psychological abuse. Second, the notary's responsibility in the event that the deed does contain misuse of circumstances, then according to the classification of the error, it must be seen whether there was an error, whether intentional by the notary or an error, due to negligence in doing certain things. KEYWORDS: Abuse of Circumstances, Notary, Responsibility of the notary.